Soil Stabilization Using Xanthan Gum: An Eco-Friendly Approach to Improve Peat Soil Properties - Sulaiman, Haspina; Yahya, Suzielahyati; Mohd Amin, Nur Alya Amirah (Disaster in Civil Engineering and Architecture, 2025)
Peat soil presents significant challenges in geotechnical engineering due to its high moisture content, low shear strength, and high compressibility, making it unsuitable for construction. Traditional stabilization methods such as cement and lime have been widely used but raise environmental concerns due to their high carbon emissions. This study explores the effectiveness of xanthan gum, a biodegradable biopolymer, as an alternative stabilizing agent for peat soil. The research aims to assess its impact on moisture content regulation, plasticity behavior, compaction characteristics, and overall soil stability. A series of laboratory experiments, including Atterberg limits tests, moisture content analysis, and compaction tests, were conducted to evaluate the engineering properties of xanthan gum-treated peat soil. Three xanthan gum concentrations (0%, 2%, and 4% by weight) were tested to determine the optimal dosage for soil stabilization. The results indicate that xanthan gum significantly reduces moisture content, with a decrease from 135.42% in untreated soil to 39.5% at 4% xanthan gum concentration. The liquid limit and plastic limit increased, indicating enhanced soil cohesion and workability. Compaction tests revealed that while 2% xanthan gum resulted in lower dry density, 4% xanthan gum improved compaction efficiency, suggesting an optimal concentration range for stabilization. The study confirms that xanthan gum is an effective, sustainable alternative to traditional soil stabilizers, providing significant benefits in peat soil stabilization. However, further research is needed to investigate its long-term durability under environmental variations, large-scale field applications, and hybrid stabilization techniques. By addressing these challenges, xanthan gum could become a mainstream solution for sustainable geotechnical engineering applications.